CASE STUDY OF DM GANGRENE WOUNDS WITH SKIN INTEGRITY DISORDERS - Andini, Sisca Pri; Aulia, Mutiara Risti; Marlina, Lina Marlina; Farozi (STIKes Budi Luhur Cimahi, 2024)
According to the World Health Organization (WHO), Indonesia is ranked 7th among the 10 countries with the highest number of sufferers, namely 10.7 million people. Complications from diabetes mellitus with diabetic gangrene rate in Indonesia is around 15%, and the amputation rate is 30%. In diabetes mellitus patients there are many nursing problems, one of which is impaired skin/tissue integrity. Diabetes mellitus is a disease caused by metabolic disorders as a result of the pancreas being unable to produce enough insulin needed by the body. A complication that often occurs in diabetes mellitus sufferers is gangrenous wounds where tissue deformity occurs either partially (Partial Thickness) or completely (Full Thickness). This study used a qualitative research design with a case study approach. The sample was 2 (two) Diabetes Mellitus patients with Gangrene Wounds with nursing problems of Skin/Tissue Integrity Disorders. The case study was carried out at Karawang District Hospital. Data collection techniques were carried out by: interviews, observation, physical examination and documentation studies. The data was analyzed narratively based on a comparison of 2 (two) patients who were processed based on the stages of the nursing process. Based on the assessment, it was found that patient 1 and patient 2 had gangreen wounds which is one of the complications that occurs in diabetes mellitus sufferers. The nursing problem that occurred was disruption of skin/tissue integrity and the implementation carried out for these two patients was wound care. The nursing problem of skin/tissue integrity disorders in both patients showed that the problem was not resolved and the intervention was continued by the nurse who was on duty in the room. Further research with another intervention and larger sample size needed to find out the best intervention for gangrene. Keywords: Diabetes Mellitus,gangrene, skin integrity